SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PEMBERIAN PENGHARGAAN BAGI PELANGGAN TERBAIK MENGGUNAKAN METODE TOPSIS - Dermi Tinambunan; Masrizal Masrizal; Ibnu Rasyid Munthe (Politeknik Bisnis Indonesia, 2023)
This study aims to solve the problem of awarding the best customers at HD Graphics companies. To make it easier for HD Graphics companies to choose the best customers to be awarded, a decision support system was built that can help make it easier for companies to select the best customers from that company. The decision support system was built using the Topsis method (Technique for Order Preference by Similarity to Ideal Solution). The criteria used consist of the percentage of customer purchases, the percentage of smooth payments by customers, customer loyalty, length of subscription, purchase intensity, and the number of cancellations by customers. The results of data processing from this research case study, obtained the 3 best customers, namely Customers 04, 06 and 01 with Vi values of 0.9478, 0.9077, and 0.8104.